MODEL KOMUNIKASI TEMAN SEBAYA DALAM PEMBENTUKAN IDENTITAS DIRI REMAJA GLOBAL MELALUI MEDIA INTERNET - Dewi K Soedarsono; Roro Retno Wulan (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
The rise of Internet Messenger (IM) has helped many individuals to connect with each other, including teenagers. In adolescence puberty fase, they were very familiar with the advancement of chatting technology in cyberspace. With consideration of the importance of communication intelligence in interacting in the virtual world, this research seeks to bring the reality of adolescent interaction with peers beyond the boundaries of geography, race, and class. The assumption of media literacy said that media literacy capability determines the position of audiences. The absence of resistance to media messages can be translated that the community does not have sufficient knowledge and experience in cyberspace. Teen life is the most important moment in human life therefore the interaction in cyberspace will determine the concept of self and ideology embedded in life later. Through phenomenology method, this research seeks to show healthy and useful internet in the formation of the identity of global adolescents. Through in-depth interviews and analysis of conversations in chat rooms, this research illustrates the positive and negative sides facing adolescents in real and virtuality life. To obtain a complete picture then, researchers also interviewed parents and teachers of the teen so that the validity of the research is maintained. The results showed that the role of parents in media literacy is very important. The intelligence of communicating in internet media especially in choosing content determined from parent guidance and peer group information. Peer group of the virtual world more influence than peer group in the real world.